Pengaruh Penambahan Air pada Pengolahan Susu Kedelai - Priscillia Picauly; Josefina Talahatu; Meitycorfrida Mailoa (AGRITEKNO: Jurnal Teknologi Pertanian, 2015)
Soybean (Glycine max (L) Merr) is needed as an alternative diversification in order to increase protein consumption. Soybean can be processed into variety of foods and drinks. The most popular drink from soybean is soya milk which is made from soybean extract yielded from the addition of water. The amount of water added determine the quality of soya milk due to its effect on the chemical and physical properties of soya milk. This research was intended to find out the proper ratio of soybean and water in the processing of soya milk to yield the best quality. A completely randomized design was used with eight treatments of soybean and water ratio as follows, ratio of 1 : 6, ratio of 1 : 8, ratio of 1 : 10, ratio of 1 : 12, ratio of 1 : 14, ratio of 1 : 16, ratio of 1 : 18 and ratio of 1 : 20. Result showed the soybean and water ratio 1 : 10 in the processing of soya milk yielded milk having good quality according to its chemical with protein content of 2.53%, fat of 1.20%, sugar total of 1.60%, pH of 7.1, and organoleptic characteristies of both somewhat sweet taste and viscous texture.